Numerical Simulation of Physical and Chemical Processes in Fluidized Bed; IOP Conference Series: Materials Science and Engineering; Vol. 93: Modern Technique and Technologies (MTT'2015) - Baturin D. A. (Power industry, 2015)
Title screen